Impact of the COVID-19 pandemic on the development of burnout syndrome in frontline physicians: prevalence and associated factors - Faria,Aline Roseane Queiroz de Paiva (2021)
SUMMARY OBJECTIVE: To evaluate the prevalence of burnout syndrome (BS) in physicians working during the COVID-19 pandemic in Paraíba and to investigate the association between BS and the sociodemographic and labor variables of these professionals. METHODS: This was a cross-sectional study including physicians who were active during the pandemic in Paraíba, whether they were on the front line (group 1) or not (group 2). Sociodemographic and labor variables were collected, and the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) questionnaire was applied. RESULTS: A total of 126 physicians were included, including 82 who were on the front line. Among the professionals with results compatible with BS, 85.5% were in group 1, compared with 14.5% in group 2, and this difference was statistically significant. At the 5% level, the variables associated with BS were age (24–33 years), not having children, working on the front line, working in the COVID-19 ICU, being on duty, and having contracted COVID-19. CONCLUSIONS: This case series found a positive association between the development of BS and medical action on the front line of the COVID-19 pandemic in Paraíba.